The orphan germinant receptor protein GerXAO (but not GerX3b) is essential for L-alanine induced germination in Clostridium botulinum Group II - Jason Brunt (Nature Portfolio, 2018)
Abstract Clostridium botulinum is an anaerobic spore forming bacterium that produces the potent botulinum neurotoxin that causes a severe and fatal neuro-paralytic disease of humans and animals (botulism). C. botulinum Group II is a psychrotrophic saccharolytic bacterium that forms spores of moderate heat resistance and is a particular hazard in minimally heated chilled foods. Spore germination is a fundamental process that allows the spore to transition to a vegetative cell and typically involves a germinant receptor (GR) that responds to environmental signals. Analysis of C. botulinum Group II genomes shows they contain a single GR cluster (gerX3b), and an additional single gerA subunit (gerXAO). Spores of C. botulinum Group II strain Eklund 17B germinated in response to the addition of L-alanine, but did not germinate following the addition of exogenous Ca2+-DPA. Insertional inactivation experiments in this strain unexpectedly revealed that the orphan GR GerXAO is essential for L-alanine stimulated germination. GerX3bA and GerX3bC affected the germination rate but were unable to induce germination in the absence of GerXAO. No role could be identified for GerX3bB. This is the first study to identify the functional germination receptor of C. botulinum Group II.